STRUKTUR KELAS DAN OTONOMI PEREMPUAN TENGGER DESA ARGOSARI KECAMATAN SENDURO KABUPATEN LUMAJANG - Aliffiati, Aliffiati; Kaler, I Ketut (Studi Budaya Nusantara, 2020)
Family and household studies are one of the initial anthropological studies related to studies beginning at the household is a study of women, specifically the role and status of women in the family / household as individuals, wives and mothers. Women in a household play a role in maintaining the stability and economic survival of thefamily, as experienced by most women in rural areas. Gender inequality that occurs in the community, especially in rural areas is one interesting problem to be studied with various approaches, one of which is the science of anthropology. The following study analyzes the Tengger ethnic women farmers in Argosari Village, Senduro District, Lumajang Regency, East Java. The research objective is to find out and identify about women's autonomy and women's social power in the family and community. Especially the social strafication of women in society is related to the status and role of women in the domestic and public spheres. The study was conducted using the ethnographic approach as a variant of the qualitative approach. Research activities include field assessments to understand the condition of the research location, followed by field data collection carried out using interviews, observation, literature, and document checks. Data collected from various sources are then processed, analyzed, then presented in the form of descriptive descriptions.